PERBANDINGAN HASIL BELAJAR SISWA MENGGUNAKAN PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) DENGAN MEDIA ULAR TANGGA DAN MEDIA PUZZLE DI KELAS XI SMA NEGERI 01 BENGKULU TENGAH - Aisha Syafitri; Hermansyah Amir; Elvinawati Elvinawati (ALOTROP, 2019)
This study aims to determine the comparison of student learning outcomes using cooperative learning type Teams Games Tournament (TGT) with media snake ladder and media puzzle in class XI SMA Negeri 01 Bengkulu Tengah Year 2017/2018 on the subject of colloidal system. This research is a quasi experimental research with the population of all students of class XI SMA Negeri 01 Bengkulu Tengah and the sample is XI MIPA 3 experiment I applying Snake Ladder media and XI MIPA 4 as experiment class II which apply puzzle media. Student learning outcomes in this study is seen from the difference between pretest and posttest values. In the experimental class I which uses snake ladder media, the average value of the increase in students' cognitive learning outcomes is 43.30. Whereas in the experimental class II that uses media puzzle, the average value of the increase in students' cognitive learning outcomes is 35.97. From a series of statistical tests conducted hypothesis testing using t-test with a significant level of 0.01 obtained tHitung> tTable (2.42> 2.39). The results showed that there was a significant difference between the learning outcomes of students who were taught by cooperative learning using Snake Media Appliance and Puzzle media. The result of this research can be concluded that  in general the result of student learning by applying cooperative learning model of Team Games Tournament (TGT) type with snake ladder media is higher than with puzzle media on colloidal system subject.